STUDI ETNOGRAFI TENTANG PERAN KONSELING KELUARGA DALAM MEMBENTUK SIKAP TOLERAN DAN EMPATI PADA SISWA SMA DI DESA TAMBANGAN KECAMATAN MANNA BENGKULU SELATAN - Karni, Asniti; Diah Safitri, Nur; Ainun Nabilla, Cindy; Afrin Siska, Betry (Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to examine the role of family counseling in fostering tolerance and empathy among high school students in Tambangan Village, Manna District, South Bengkulu. The background of this research highlights the importance of character education through family counseling in addressing complex social challenges. This study offers novelty by employing an ethnographic approach to deeply explore family and student experiences in the counseling process. The qualitative methodology includes participatory observation, in-depth interviews, and document analysis. The results indicate that family counseling significantly contributes to enhancing students' tolerance and empathy through open communication, emotional support, and parental role modeling. Furthermore, the study finds that collaboration between schools and families strengthens the effectiveness of counseling. This research provides valuable insights for developing more effective family counseling models to shape students' character.